Peran Humas PT. Private Sanctuary dalam Meningkatkan Citra Media Sosial di Kuta Mandalika Lombok Tengah - Devi, Ni Nyoman Indira Chaitra; Arjana, Ida Bagus Made (Jurnal Komunikasi Nusantara, 2024)
This study aims to analyze the role of Public Relations (PR) in enhancing the image of Private Sanctuary through social media by employing a qualitative approach and utilizing domain analysis, taxonomic analysis, compositional analysis, and cultural theme analysis. The research was conducted at the Private Sanctuary office in Kuta Mandalika, Central Lombok, focusing on the company's social media platforms, such as Instagram, Facebook, and Twitter. Primary data were obtained through in-depth interviews with the PR team and observations of published social media content, while secondary data were gathered from company documentation and reports. Through data analysis involving triangulation techniques from interviews, observations, and documentation, the study identifies communication strategies employed by the PR team to build the company's positive image on social media and their impact on audience engagement, particularly among younger generations. The findings reveal that while Private Sanctuary has successfully utilized social media to showcase its social and educational commitments, the main challenge lies in creating more engaging and interactive content for younger audiences. This study provides insights into how culture, social norms, and communication strategies influence audience perception and engagement with the company on digital platforms. Abstrak Penelitian ini bertujuan untuk menganalisis peran Hubungan Masyarakat (Humas) dalam meningkatkan citra Private Sanctuary melalui media sosial dengan menggunakan pendekatan kualitatif dan metode analisis domain, analisis taksotomi, analisis komposisional, dan analisis tema kultural. Penelitian dilakukan di kantor Private Sanctuary di Kuta Mandalika, Lombok Tengah, dengan fokus pada platform media sosial perusahaan seperti Instagram, Facebook, dan Twitter. Data primer diperoleh melalui wawancara mendalam dengan tim Humas dan observasi terhadap konten yang dipublikasikan di media sosial, sementara data sekunder didapatkan dari dokumentasi dan laporan perusahaan. Melalui analisis data yang melibatkan teknik triangulasi dari wawancara, observasi, dan dokumentasi, penelitian ini mengidentifikasi strategi komunikasi yang digunakan oleh tim Humas untuk membangun citra positif perusahaan di media sosial, serta dampaknya terhadap keterlibatan audiens, terutama generasi muda. Hasil penelitian menunjukkan bahwa meskipun Private Sanctuary telah sukses memanfaatkan media sosial untuk menunjukkan komitmen sosial dan pendidikan, tantangan utama terletak pada menciptakan konten yang lebih menarik dan interaktif untuk audiens muda. Penelitian ini memberikan wawasan tentang bagaimana budaya, norma sosial, dan strategi komunikasi mempengaruhi persepsi dan keterlibatan audiens terhadap perusahaan di platform digital.